Potential of Okra as a hyperaccumulator plant under cadmium exposure - Mariappan Mahalakshmi; Ammaiyappan Selvam (The Bioscan, 2025)
Cadmium (Cd) is a non-essential element and one of the most toxic heavy metals due to its high toxicity for all living organisms. It is easily taken in by plants owing to its high bioavailability, enters the food chain and threatens people's health. Okra (Abelmoschus esculentus) was examined for phytoremediation purposes with the focus on accumulation of Cd and physiological mechanisms of Cd tolerance. Pot experiment for 60days was conducted to investigate the effects of different concentrations of Cd (0, 5, 25, 50, 100 and 250 mg kg-1 Cd in soil) on okra plant through different physiological and biochemical parameters: plant dry matter content, leaf pigment content, leaf soluble protein, proline activity, antioxidant enzyme of peroxidase (POD) and Cd content. Exposure to Cd enhanced plant growth at 50 mg kg-1 without showing symptoms of visible damage and when the Cd concentrations increased to 100 and 250 mg kg-1, the okra biomass were reduced through increasing Cd-stress. The activity of POD was significantly enhanced with increase in Cd concentration. The Cd accumulation in the shoots (stems and leaves) of okra was lower than that in roots and the Cd content in the shoots increased with increasing Cd concentration. The fruit Cd content decreased with increasing Cd treatment which indicated limited ability of transferring Cd from root to fruit. This study suggests that okra has some remediation ability against heavy metal polluted contaminated soil and has potential to decontaminate Cd-polluted soil.